Micro-computed tomographic analysis of the marginal adaptation of a calcium silicate-based cement to radicular dentin after removal of three different intracanal medicaments - an in vitro study - Jain, Ruchika Nirmal; Abraham, Sathish; Karad, Rohini Ramesh; Najan, Harshal Balasaheb; Vaswani, Sneha Dhruvkumar; Torris, Arun (Journal of Conservative Dentistry, 2021)
<p style="box-sizing: inherit; line-height: 1.5; margin-top: 1.2rem; margin-bottom: 1.2rem; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Context: This study focuses on the marginal adaptation of a calcium silicate-based cement to the root dentin after retrieval of different intracanal medicaments. <p style="box-sizing: inherit; line-height: 1.5; margin-top: 1.2rem; margin-bottom: 1.2rem; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Aim: This study compared the marginal adaptation of a calcium silicate-based cement to radicular dentin in the apical third of the root canal following the use of three different intracanal medicaments. <p style="box-sizing: inherit; line-height: 1.5; margin-top: 1.2rem; margin-bottom: 1.2rem; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Materials and methods: Forty single-rooted premolar teeth (n = 40) were decoronated 13 mm above the root apices; then, 3 mm of the root tips were resected to standardize the root length. Orthograde cleaning and shaping were done using the rotary files and apical enlargement using peeso reamers. Depending on the intracanal medicament used, the samples were equally divided into four groups: Group 1 - control, Group 2 - Metapex, Group 3 - triple antibiotic paste (TAP), and Group 4 - calcium hydroxide with Propolis. Subsequently, the medicament was removed and a 3 mm apical barrier of BiodentineTM was placed and later scanned using an ex vivo micro-computed tomography scanner.